On extension of the Sturm-Liouville oscillation theory to problems with pulse parameters - Zvereva, M. B.; Pokornyi, Yu. V.; Shabrov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Oscillation spectral properties (the number of zeros, their alternation for eigenfunctions, the simplicity of the spectrum, etc.) are described for the Sturm-Liouville problem with generalized coefficients.